Supporting trans people in libraries - Krueger, Stephen G. (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2019)
"As trans people (including those on the nonbinary spectrum) start to feel safer expressing their identities in public, libraries are making an effort to show that they welcome people of all gender identities. Yet there are many potential barriers to actively supporting trans people, including lack of knowledge about the needs of the trans community and lack of funding or institutional support. This book, written entirely by trans library workers, is designed to dismantle some of these barriers. Supporting Trans People in Libraries is relevant for library workers of any background and position. People with little knowledge about trans identities can start with the opening introductory chapters, while those looking for guidance on a specific situation--such as adding all-gender restrooms, interacting respectfully with trans coworkers, deciding what information to require on library card applications, writing inclusive job postings, making collection development decisions, and more--can jump to a particular chapter. For each topic, there are sections on easy fixes, best practices, and example language. Readers can easily adapt the information to benefit their libraries and communities in concrete ways"--Publisher's description